Evaluation of Salivary Albumin in Diabetic Patients - PB Vaziri; M Vahedi; SH Abdollahzadeh; HR Abdolsamadi; M Hajilooi; SH Kasraee (Tehran University of Medical Sciences, 2009)
Background: The clinical symptoms of diabetes mellitus in oral cavity are xerostomia, pathological changes in periodontal tissues and caries. It has been suggested that the determination of salvia`s components in diabetic patients may be useful in describing and further understanding the oral findings in this condition. The aim of this study was to detect differences between the salivary albumin in diabetic patients and healthy people. Methods: A case-control study was carried out using data from Hamadan researches diabetes center in 2008. We selected 40 patients with type 1 diabetes mellitus aged 9-61 years, 40 patients with type2 aged 39-82 years and 40 healthy controls aged 20-67 years. Dental and oral status was assessed for all subjects. Completely unstimulated saliva samples were collected from diabetic patients and control subjects. Nephelometric method was used to determine salivary albumin concentration. Statistical analysis was done by SPSS. Results: No significant difference in salivary albumin concentration was found between the control group and type1 diabetic patients but salivary albumin was significantly higher in type2 diabetic patients in compare with control groups (P= 0.017), also no significant difference was found between type1 and type2 diabetic patients. In diabetic patients, complain of dry mouth and burning feeling in mouth was significantly higher, as well as, dental examinations showed higher DMFT mean values than the controls. Conclusion: Adults with type2 diabetes mellitus have higher concentration of salivary albumin that would play a helpful diagnostic role in oral findings of diabetic patients.